2010
DOI: 10.1108/13581981011093695
|View full text |Cite
|
Sign up to set email alerts
|

Shari'asupervision of Islamic financial institutions

Abstract: Purpose -The governance structure of Islamic financial institutions (IFIs) implements Islamic canon law (Shari'a) into business transactions through Shari'a supervision processes. This paper aims to define Shari'a supervision and examine Shari'a supervisory councils (both within and outside the Central Bank), Shari'a consulting firms, Shari'a advisors, and Shari'a Supervisory Boards (SSB). It also discusses the importance of the hierarchical position of SSBs and evaluates their objectives and functions. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 6 publications
(3 reference statements)
0
40
0
Order By: Relevance
“…According to Charles dan Chariri (2012), the party holding the role in the implementation and disclosure of the ISR is the SSB. SSB occupies a strategic position in the hierarchy of Islamic financial institutions (Nathan Garas & Pierce, 2010). SSB has the same authority and position in Islamic financial institutions as the board of commissioners (Farook et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…According to Charles dan Chariri (2012), the party holding the role in the implementation and disclosure of the ISR is the SSB. SSB occupies a strategic position in the hierarchy of Islamic financial institutions (Nathan Garas & Pierce, 2010). SSB has the same authority and position in Islamic financial institutions as the board of commissioners (Farook et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Idrees (2014) argues that it is the responsibility of supervisory board to analyze the actions and behaviors of individuals and institutions in order to certify that these are all Sharī'ah compliant. The SSB is an independent body with members that are qualified in Islamic studies or have fiqh knowledge and are aware of financial transactions in accordance with Sharī'ah rules and regulations (Garas & Pierce, 2010). The functions and duties of SSBs are more or less same in different countries but comprise different number and nature of members (Akbar, 2008;Charles & Chariri, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…First is the supervisory function and second is the consultative function. The supervisory function deals with issuance of fatwá and giving approval to new products while the consultative function is the means to calculate due zakāh and giving solutions that are Sharī'ah compliant during the implementation of contracts (Garas & Pierce, 2010). The position and authority of SSB is equivalent to board of commissioners in the IB and are sometimes treated as external auditors (Farook, Hassan & Lanis, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(Mejia et al, 2014). Garas and Pierce (2010) commenting on the sharia supervision in Islamic financial institutions (IFI), observed that it can assume different forms at macro and micro levels in different countries. At the macro level, Sharia supervision could be conducted by national or regional Sharia Supreme Councils and at the micro level, it can be conducted by Sharia Supervisory Board, Sharia Consulting firms or a single Sharia advisor.…”
Section: Literature Reviewmentioning
confidence: 99%